Systematic Review of Primary Hyperparathyroidism in India: The Past, Present, and the Future Trends - P. V. Pradeep; B. Jayashree; Anjali Mishra; S. K. Mishra (International Journal of Endocrinology)
Primary hyperparathyroidism (PHPT) has become an asymptomatic disease in the Western world with the introduction of routine calcium screening. However, the same phenomenon is not observed in India. We have now systematically reviewed the status of PHPT in India. While there is a paucity of literature on PHPT from India when compared to Western countries, some information can be gleaned upon. Most patients present with symptomatic disease whereas very few are screen-detected cases (bone disease 77%, renal disease 36%, and 5.6% asymptomatic). Mean calcium, parathyroid hormone (PTH), and alkaline phosphate levels are high while Vitamin D levels are low. The average parathyroid gland weight is large and the majority being parathyroid adenomas (89.1%). Hungry bone syndrome (HBS) is common in the postoperative period. The disease-related mortality rate is 7.4%, recurrence 4.16%, and persistent disease 2.17%. We suggest that dedicated efforts are needed to pick up asymptomatic disease in India by methods like incorporating calcium estimation in the routine health check-up programs.